Peptide sequences by mass spectrometry : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University - Kent, Stephen Brian Henry (Massey University, 1970)
The preparation and mass spectrometry of permethylated peptide derivatives was investigated. Procedures for the modification of free peptides prior to permethylation were examined. Acetylation with methanol+ acetic anhydride was found to result in partial esterification of the peptide. Specific cleavage of the C-terminal residue was also observed; a mechanism is proposed for this reaction. Esterification with HCl in methanol followed by acetylation of the peptide ester gave a mixture of products due to random methanolysis during the esterification. Methods of acetylating free peptides were examined, and it was found that the use of water + acetic anhydride at room temperature resulted in rapid quantitative acetylation, with no significant side reactions. Reaction of an ethereal solution of diazomethane with the acetyl-peptide gave quantitative esterification with negligible byproduct formation. Use of dimethylsulfinyl sodium in dimethylsulfoxide, and methyl iodide for the permethylation of peptide derivatives was investigated. Suitable conditions were found for the preparation of the reagent and for its use in the permethylation reaction. Substitution at existing ester groups was found to occur during the permethylation, and the products were partially characterised. Use of the free acetyl-peptide rather than its methyl ester eliminated this side reaction. Introduction of more than the expected number of methyl groups was observed. This extra-methylation was found to occur mainly at specific residues, although some random methylation was observed. The conditions of permethylation were adjusted to minimise extra-methylation and limit it to specific sites in the molecule. Peptides containing aspartyl residues undergo chain cleavage; the products of this reaction were identified and a mechanism proposed for their formation. The permethylation reaction is discussed in relation to the formation of these artefacts; it is thought to involve deprotonation of the peptide to form a multiple anion. Reaction conditions are suggested to eliminate these side reactions. The mass spectrometry of permethylated peptide derivatives is discussed and the mass spectra of peptides of known sequence reported. The mass spectra show the sequence-determining fragments as the principal ions. This observation is rationalised in terms of the negative-inductive effect of the N-methyl groups. The simple procedure for interpreting the mass spectra of permethylated peptide derivatives is outlined, together with the use of minor fragmentation modes in identifying the molecular ion and sequencing peaks. Deuteriated methyl iodide, high resolution mass spectrometry and the detection of metastable transitions can all be used to confirm the deduced sequence. The techniques developed were applied to a mixture of free peptides isolated from cheese; the three peptides present were sequenced. The results were confirmed by high resolution mass measurement and permethylation with deuteriated methyl iodide. The present state of peptide sequence determination by mass spectometry is evaluated and possible future developments discussed.
Keywords: Mass spectrometry; Peptides; Analysis